2010
DOI: 10.5301/ejo.2010.6117
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Optical Coherence Tomography Outcomes of Intravitreal Bevacizumab and Ranibizumab in Inflammatory Choroidal Neovascularization Secondary to Punctate Inner Choroidopathy

Abstract: Over a 1-year period, bevacizumab and ranibizumab can be safely and successfully used to treat inflammatory CNV secondary to PIC, avoiding the need for systemic immunosuppression in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In addition, Kramer et al reported that in patients with choroidal neovascularization related to inflammatory diseases, intravitreal injections of bevacizumab on an as-needed basis resolved leakage and subretinal fluid and improved visal acuity [27]. Several recent studies have reported that anti-VEGF agents, bevacizumab and ranibizumab were efficacious in treating CNV secondary to PIC [8, 28, 29]. Particularly, a case series study found that intravitreal anti-VEGF resolved CNV secondary to PIC over a 3–28 months follow-up period [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Kramer et al reported that in patients with choroidal neovascularization related to inflammatory diseases, intravitreal injections of bevacizumab on an as-needed basis resolved leakage and subretinal fluid and improved visal acuity [27]. Several recent studies have reported that anti-VEGF agents, bevacizumab and ranibizumab were efficacious in treating CNV secondary to PIC [8, 28, 29]. Particularly, a case series study found that intravitreal anti-VEGF resolved CNV secondary to PIC over a 3–28 months follow-up period [10].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective case series, Mansour et al [29] found that intravitreal injection of bevacizumab improved BCVA by 2.2 lines on average in treated PIC eyes with CNV. Cornish et al [8] showed that BCVA of 11.1% treated eyes deteriorated one year after intravitreal bevacizumab or ranibizumab injection. In our study, no treated eyes showed a decrease in BCVA; however, because of the differences in study designs and other factors, the studies are not directly comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these studies local or systemic steroid therapy was associated, and in two of them [25, 31] immunosuppressive drug was used in the majority of patients. Subsequently in the following years, the use of anti-VEGF therapy increased and IVB became available; 12 case series and 2 comparative retrospective studies about the IVB treatment in uveitis-related CNV are reported (Lott et al [38] and Cornish et al [45]). The first compares PDT to IVB in MC and the second IVB to IVR in PIC, but only in few cases.…”
Section: Therapy and Clinical Studiesmentioning
confidence: 99%
“…Both have come into increasing use as intravitreal agents in the treatment of choroidal neovascular membranes (CNVM) secondary to numerous etiologies, including exudative AMD, myopia, punctate inner choroidopathy, Best's vitelliform dystrophy, angioid streaks, and idiopathic CNVM, among others. [1][2][3][4][5] Sorsby macular dystrophy is characterized by bilateral CNVM typically associated with midperipheral drusen and presenting in the fourth to fifth decade of life, and associated with mutations in the tissue inhibitor of the metalloproteinase-3 (TIMP 3) gene. 6,7 Argon laser has proven ineffective for the juxtafoveal or extrafoveal CNVM.…”
Section: Introductionmentioning
confidence: 99%